Numerical Analysis of Pulse Decay Characteristics in Solid Rocket Motors for Different Finocyl Grain Configurations - Fengnan Guo; Fengrui Li; Hongfeng Ji; Lin Fu; Xuyang Gao (Aerospace)
Combustion instability is an abnormal working state that often occurs in advanced solid rocket motors (SRMs), which can arouse pressure oscillations, increase the risk of mission failure, and even cause structural damage. In this paper, a numerical simulation method is adapted to analyze the combustion instability problem of a typical finocyl grain SRM, and the working process and pressure oscillation of different-structure SRMs are compared and analyzed. Firstly, the acoustic finite element analysis (FEA) method and the large eddy simulation (LES) method for SRM combustion instability analysis are given. Then, the numerical simulation method presented in this paper is verified by comparing the present results with the experimental data of Ariane-5 P230 motor, and finally, the pressure oscillation characteristics of SRMs with different structures by external pulse excitation are studied. The simulation results show that the pressure decay rate of the front finocyl grain structure is faster than that of the rear finocyl grain structure under the same external excitation. The excitation position has a relatively minor influence on the decay characteristics of pressure oscillations. The results can provide a certain reference for the combustion stability design of SRMs.